PREVALENCE OF OVERWEIGHT AND OBESITY AND THEIR CORRELATION WITH FASTING BLOOD GLUCOSE AND BLOOD PRESSURE AMONG FEMALE SECONDARY SCHOOL STUDENTS IN KANO, NIGERIA - Mukhtar, I. G.; Zaituna, Nasir Yahya (FUDMA JOURNAL OF SCIENCES, 2024)
Childhood obesity has been linked with adverse cardiometabolic risk. Multiple indices have been used to assess obesity and associated cardiovascular risk. However, relationship between these indices and markers of cardiovascular risk has been inconsistent. This study aimed to determine prevalence of overweight and obesity and their correlation with fasting blood glucose (FBG) and measures of blood pressure among female secondary school students in Kano, Nigeria. One hundred and fifty female students were recruited. Fasting blood glucose was measured using glucose oxidase method. Anthropometric indices and blood pressure measurements were by standard protocols. Mean age of the participants was 15.67 ± 1.30 years (13 – 18 years). Mean systolic, diastolic, and arterial blood pressure were: 115.38 ± 7.62, 71.01 ± 8.34, and 85.65 ± 6.58 mmHg respectively. Mean anthropometric indices were: weight - 48.30 ± 8.85 kg, height - 1.58 ± 0.07 m, BMI -  19.43 ± 3.82 kg/m2 hip circumference (HC) - 71.69 ± 15.14 cm, waist circumference (WC) - 62.05 ± 10.34 cm, waist to height ratio (WHtR) - 0.40 ± 0.07, and waist-to-hip ratio (WHC) - 0.88 ± 0.28, respectively. Mean FBG was 4.55 ± 0.28 mmol/l. Prevalence of overweight and obesity were: 6.0% and 5.3% respectively. None of the anthropometric indices correlated with FBG or blood pressure. Prevalence of overweight and obesity in adolescent female students in this environment are low and is not correlated with fasting blood glucose or blood pressure.
Keywords: Adolescents; Female; Kano; Prevalence; Obesity